Hollow energy-saving glass and manufacturing method thereof

CN122916463APending Publication Date: 2026-10-16SHUYANG JUNNUO GLASS TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611092322.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,现有中空玻璃仍存在隔热保温性能不佳导致的节能效果差的问题,无法满足特定环境的使用需求

Benefits of technology

[0023] This invention involves coating a glass substrate with a titanium dioxide film. By pretreating the glass substrate with a sodium hydroxide solution and varying the concentration of the sodium hydroxide solution, the specific surface area of ​​the glass substrate can be increased, thereby enhancing the titanium dioxide loading. By altering the amount of anhydrous ethanol added, the calcination time, and the calcination temperature, the cross-linking of titanium micelles can be promoted, further increasing the titanium dioxide loading and ensuring the titanium dioxide sol is fully cured. This improves the adhesion between the coating and the glass substrate, resulting in insulated energy-saving glass that exhibits excellent thermal insulation performance, effectively reducing building energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916463A_ABST
    Figure CN122916463A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of hollow glass, in particular to a kind of hollow energy-saving glass and its manufacturing method.The present application overcomes the problem of poor energy-saving effect caused by poor heat insulation performance of hollow glass.The present application changes the concentration of sodium hydroxide solution, the amount of anhydrous ethanol, calcination time and calcination temperature;Prepares desiccant and changes the ratio of attapulgite, silica powder and active alumina, drying temperature, calcination time, calcination temperature, additive type, immersion time and polymerization temperature;Change butyl glue coating machine coating temperature, extrusion gas pressure, glue speed and structural glue type;Change the volume ratio of argon and nitrogen in gas and the percentage of gas volume in hollow layer volume;Change the percentage of desiccant filling and the thickness of hollow layer, and the energy-saving effect of the prepared hollow energy-saving glass is significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of insulated glass technology, specifically to an insulated energy-saving glass and its manufacturing method. Background Technology

[0002] Glass is a primary material used in building curtain walls and exterior windows. One-third of a building's energy consumption is lost through glass conduction; therefore, improving the energy-saving performance of glass is crucial. Energy-saving glass refers to glass products with good heat insulation and thermal insulation properties, designed to improve building energy efficiency and reduce energy consumption. Types include heat-absorbing glass, heat-reflective glass, low-emissivity glass, insulated glass, vacuum glass, and ordinary glass. Among these, insulated glass, due to its low heat transfer coefficient, is currently the most ideal energy-saving building glass.

[0003] Chinese patent CN116239318B discloses an insulated energy-saving glass and its preparation method. This invention involves preparing modified polysiloxane and nano-sized strontium cerium bismuthate, combining the two to create a heat-reflective coating, which is then applied to the surface of the glass substrate. The resulting insulated glass exhibits improved heat reflectivity, mechanical properties, and weather resistance, as well as better resistance to temperature changes and adhesion. However, during long-term use, butyl sealant may leak into weak points in the seal, leading to a decrease in the heat insulation performance of the insulated glass and poor energy-saving effect.

[0004] Chinese patent CN109534691B discloses an energy-saving film, laminated glass, insulated glass, and its applications. This invention, by modifying the fabrication processes of the dielectric layer, functional layer, and protective dielectric layer, prepares an energy-saving film and applies it to insulated glass. This effectively reduces the absorption of solar radiation by the glass substrate, resulting in good energy-saving performance. It can be used on both the inner and outer surfaces of insulated glass. However, the energy-saving effect of the insulated glass produced by this invention still needs further improvement.

[0005] With the increasing demands for energy conservation and environmental protection in modern buildings, insulated glass has been widely used due to its excellent heat insulation and sound insulation properties. However, existing insulated glass still suffers from poor heat insulation performance, resulting in poor energy-saving effects and failing to meet the needs of specific environments.

[0006] Therefore, a hollow energy-saving glass and its manufacturing method are proposed. Summary of the Invention

[0007] The purpose of this invention is to provide a hollow energy-saving glass and its manufacturing method.

[0008] To achieve the above objectives, the present invention provides the following technical solution:

[0009] The manufacturing method of insulated energy-saving glass is as follows:

[0010] Pretreated glass substrate is obtained by pretreating the glass substrate with a 12-18 wt% sodium hydroxide solution; titanium dioxide sol is obtained by mixing 51-72 parts by weight of anhydrous ethanol, tetrabutyl titanate, glacial acetic acid, deionized water and 1M hydrochloric acid solution and letting it stand overnight at room temperature; the pretreated glass substrate is added to the titanium dioxide sol, ultrasonicated, washed and dried, and calcined at 300-400℃ for 1-1.5 h to obtain coated glass substrate;

[0011] Attapulgite, silica powder, and additives are mixed evenly in a ratio of 2-4:1-2:0.5-1.5 to obtain material one; material one is baked, extruded, and dried at 110-180℃ to obtain material two; material two is crushed, sieved, and calcined at 380-420℃ for 1-1.8h to obtain a desiccant.

[0012] A desiccant is filled into the spacer frame to obtain a filled spacer frame; a butyl rubber coating machine is used to evenly coat the filled spacer frame with butyl rubber at a temperature of 135-160℃, an extrusion pressure of 0.5-1.5MPa, and a coating speed of 20-35m / min to obtain a coated spacer frame; two coated glass substrates are bonded to the coated spacer frame respectively, fixed, and pressed to obtain a rough finished product; structural adhesive is applied to the joint between the coated glass substrate and the coated spacer frame to obtain a glued rough finished product; gas is filled into the glued rough product and sealed to obtain insulated energy-saving glass; the gas is argon and nitrogen, with a volume ratio of 3-8:1.2-2.2.

[0013] Preferably, the method for preparing the coated glass substrate is as follows: The glass substrate is ultrasonically cleaned in anhydrous ethanol for 20 minutes to obtain a cleaned glass substrate; the cleaned glass substrate is ultrasonically cleaned in sodium hydroxide solution for 2 hours, washed with distilled water, and dried at 100°C for 10 hours to obtain a pretreated glass substrate; 2 / 3 of the total amount of anhydrous ethanol, tetrabutyl titanate, and glacial acetic acid are added to a flask at 30°C to obtain mixture one; the remaining 1 / 3 of the anhydrous ethanol, deionized water, and 1M hydrochloric acid solution are mixed and added dropwise to mixture one to obtain mixture two; the pH value of mixture two is 3.5; mixture two is allowed to stand overnight at room temperature to obtain titanium dioxide sol; the pretreated glass substrate is added to the titanium dioxide sol, ultrasonicated for 1 hour, washed with anhydrous ethanol, dried at 70°C for 10 hours, and calcined to obtain the coated glass substrate.

[0014] Preferably, the desiccant is prepared as follows: Attapulgite, silica gel powder and additives are mixed evenly to obtain material one; material one is baked at a constant temperature of 128°C for 1.5 hours, and spherical particles with a diameter of 2 mm are extruded using an extruder and dried to obtain material two; material two is crushed, sieved and then calcined to obtain the desiccant.

[0015] Preferably, the additive is one of activated alumina, magnesium sulfate, montmorillonite, or modified molecular sieve.

[0016] Preferably, the modified molecular sieve is prepared as follows: N-isopropylacrylamide is dissolved in ethanol, benzoyl peroxide is added, and the mixture is stirred at room temperature to obtain a clear solution; molecular sieve is added to the clear solution and impregnated for 2.5-3 hours, and then dried to obtain a mixed material; the mixed material is subjected to a polymerization reaction at 85-110℃ to obtain a polymerized material; the polymerized material is washed and dried using chloroform and ethanol to obtain the modified molecular sieve.

[0017] Preferably, the butyl rubber coating machine has a temperature of 140℃, an extrusion air pressure of 1.2MPa, and a dispensing speed of 25m / min.

[0018] Preferably, the structural adhesive is one of silicone adhesive, polyurethane adhesive, or acrylic adhesive.

[0019] Preferably, the volume percentage of the gas is 55%-95% of the volume of the hollow layer; the volume ratio of argon to nitrogen is 4-7.8:1.2-2.

[0020] Preferably, there is a hollow layer between the two coated glass substrates; the thickness of the hollow layer is 6-15mm; and the desiccant filling percentage is 50%-85%.

[0021] Another aspect of the present invention provides an insulated energy-saving glass, which includes a glass substrate, a spacer frame, butyl sealant, structural adhesive, desiccant, argon gas, and nitrogen gas.

[0022] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0023] This invention involves coating a glass substrate with a titanium dioxide film. By pretreating the glass substrate with a sodium hydroxide solution and varying the concentration of the sodium hydroxide solution, the specific surface area of ​​the glass substrate can be increased, thereby enhancing the titanium dioxide loading. By altering the amount of anhydrous ethanol added, the calcination time, and the calcination temperature, the cross-linking of titanium micelles can be promoted, further increasing the titanium dioxide loading and ensuring the titanium dioxide sol is fully cured. This improves the adhesion between the coating and the glass substrate, resulting in insulated energy-saving glass that exhibits excellent thermal insulation performance, effectively reducing building energy consumption.

[0024] 2. This invention, by preparing a desiccant and changing the ratio of attapulgite, silica gel powder, and activated alumina, as well as the drying temperature, calcination time, calcination temperature, type of additives, impregnation time, and polymerization temperature, helps to form and stabilize the internal chemical bonds of the material, enhances the moisture absorption performance of the desiccant, and can also increase the specific surface area and pore volume of the material, improve the adsorption capacity of the desiccant, thereby improving the heat insulation performance of the insulated glass and enhancing the energy-saving effect.

[0025] 3. By changing the coating temperature, extrusion pressure, dispensing speed, and type of structural adhesive in the butyl rubber coating machine, this invention can achieve a moderate viscosity and enhanced fluidity of the butyl rubber, forming a uniform and continuous coating on the spacer frame. This avoids phenomena such as bubbles or adhesive breaks. Combined with the excellent sealing properties of the structural adhesive, the sealing performance of the insulating glass can be improved, preventing impurities such as air and moisture from entering the insulating layer and damaging its thermal insulation effect. As a result, the energy-saving effect of the resulting energy-saving insulating glass is enhanced.

[0026] 4. This invention, by changing the volume ratio of argon and nitrogen in the gas, enables insulated glass to possess excellent thermal insulation performance, environmental protection performance, and lower cost. By changing the percentage of the gas volume in the insulated layer, in addition to improving thermal insulation performance, it can also reduce moisture inside the glass, slow down the oxidation of the spacer frame and the aging of the desiccant, and extend the service life of the glass. By changing the desiccant filling percentage and the thickness of the insulated layer, it can effectively maintain the temperature stability of the glass surface, reduce heat transfer paths, reduce condensation and fogging caused by excessive temperature differences, and keep the inside of the insulated glass dry. The combined effect of these two factors significantly improves the thermal insulation performance of the insulated glass, thereby enhancing energy-saving performance. Attached Figure Description

[0027] Figure 1 The figures show the test results of the thermal insulation performance of the insulated energy-saving glass in Embodiments 2 and 5-9 of the present invention. Detailed Implementation

[0028] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0029] Please see Figure 1 This invention provides a hollow energy-saving glass and its manufacturing method, the technical solution of which is as follows:

[0030] The material information involved in this invention is as follows:

[0031] Anhydrous ethanol CAS: 64-17-5; Tetrabutyl titanate CAS: 5593-70-4; Glacial acetic acid CAS: 64-19-7; Hydrochloric acid CAS: 7647-01-0; Attapulgite CAS: 12174-11-7, particle size 200-325 mesh, specific surface area 150-220 m² 2 / g; Silica gel powder CAS: 112926-00-8, average pore size 2.0-3.0nm, particle size 200-400 mesh, specific surface area 600-800m²2 / g; Activated alumina CAS: 1302-74-5, particle size 200-300 mesh, specific surface area 280-350m² 2 / g, pore volume is 0.40-0.52L / g; magnesium sulfate CAS: 7487-88-9; N-isopropylacrylamide CAS: 2210-25-5; benzoyl peroxide CAS: 94-36-0; chloroform CAS: 67-66-3; butyl rubber was purchased from Sinochem Pharmaceutical Co., Ltd.; silicone sealant was purchased from Guangzhou Baiyun Technology Co., Ltd.; polyurethane sealant was purchased from Meibang (Huangshan) Adhesive Co., Ltd.; acrylic sealant was purchased from Shenzhen Jingyi Chemical Co., Ltd.; molecular sieve is type 3A molecular sieve, purchased from Shanghai Yuanye Biotechnology Co., Ltd., item number V34021; montmorillonite was purchased from Shanghai Yuanye Biotechnology Co., Ltd., item number S35959.

[0032] Example 1

[0033] The glass substrate was ultrasonically cleaned in anhydrous ethanol for 20 min to obtain a cleaned glass substrate. The cleaned glass substrate was then ultrasonically cleaned in a 12 wt% sodium hydroxide solution for 2 h, washed with distilled water, and dried at 100℃ for 10 h to obtain a pretreated glass substrate. Two-thirds of the total anhydrous ethanol, 25 parts of tetrabutyl titanate, and 7 parts of glacial acetic acid were added to a flask at 30℃ to obtain mixture one. The remaining one-third of the anhydrous ethanol, 12 parts of deionized water, and 1 part of 1M hydrochloric acid solution were mixed and added dropwise to mixture one to obtain mixture two. The pH of mixture two was 3.5. Mixture two was allowed to stand overnight at room temperature to obtain a titanium dioxide sol. The pretreated glass substrate was added to the titanium dioxide sol, ultrasonicated for 1 h, washed with anhydrous ethanol, dried at 70℃ for 10 h, and calcined at 300℃ for 1 h to obtain a coated glass substrate. The total amount of anhydrous ethanol added was 51 parts by weight. The ultrasonic parameters were as follows: ultrasonic frequency 40 kHz, power density 150 W / L.

[0034] Attapulgite, silica powder, and additive activated alumina were mixed evenly in a ratio of 2:1:0.5 to obtain material one; material one was baked at a constant temperature of 128℃ for 1.5 hours, and extruded into spherical particles with a diameter of 2 mm using an extruder, and dried at 110℃ to obtain material two; material two was crushed and passed through a 50-mesh sieve, and calcined at 380℃ for 1 hour to obtain a desiccant.

[0035] A desiccant is filled into the spacer frame to obtain a filled spacer frame; butyl sealant is evenly coated onto the filled spacer frame using a butyl sealant coating machine at a temperature of 135℃, an extrusion pressure of 0.5MPa, and a coating speed of 20m / min to obtain a coated spacer frame; two coated glass substrates are bonded to the coated spacer frame respectively, fixed, and pressed to obtain a rough finished product; structural silicone sealant is applied to the joint between the coated glass substrate and the spacer frame to obtain a glued rough finished product; gas is filled into the glued rough product and sealed to obtain an insulated energy-saving glass; the gas is a mixture of argon and nitrogen in a volume ratio of 3:1.2; the gas volume ratio is 55%-95% of the insulated layer volume; the desiccant filling percentage is 50%; the insulated layer thickness is 6mm.

[0036] Example 2-14

[0037] The preparation method and parameters of Example 1 are similar, with specific differences shown in Table 1.

[0038] Table 1 Specific preparation parameters for Examples 2-14

[0039]

[0040] Comparative Example 1

[0041] Insulating energy-saving glass was prepared according to the method of Example 1, but the difference was that sodium hydroxide solution was not used to pretreat the glass substrate.

[0042] Example 15 Thermal Insulation Performance Test

[0043] The heat transfer coefficient of insulated energy-saving glass was tested according to the method in GB / T 22476-2008 "Calculation and determination of steady-state U-value (heat transfer coefficient) of insulated glass".

[0044] According to GB / T2680-2021 "Determination of Visible Light Transmittance, Direct Solar Transmittance, Total Solar Transmittance, Ultraviolet Transmittance and Related Window Glass Parameters of Architectural Glass", the visible light transmittance and direct solar transmittance of insulated energy-saving glass were tested; the results are shown in Table 2.

[0045] Table 2 Thermal insulation performance tests of Examples 1-14

[0046]

[0047] Pretreatment of the glass substrate with sodium hydroxide solution can remove impurities from the surface and increase the content of surface silanol groups, thereby improving the titanium dioxide loading. Therefore, the surface modification by alkali has a significant impact on the titanium dioxide coating. Table 2 shows that in Examples 1-4, increasing the concentration of sodium hydroxide solution allows for more intense etching of the glass surface, forming more micropores and a rougher structure. This is beneficial for the subsequent adhesion of the titanium dioxide sol, as the sol can more easily penetrate into these micropores. However, excessively high concentrations of sodium hydroxide solution may lead to over-etching of the glass surface, even damaging the structural integrity of the glass, resulting in a decrease in the thermal insulation performance of the insulated glass. In Example 2, when the concentration of sodium hydroxide solution is 14 wt%, the titanium dioxide loading can be maximized, improving the thermal insulation performance of the insulated glass. Figure 1 As can be seen, in Examples 2 and 5-9, changing the amount of anhydrous ethanol added affects the loading of titanium dioxide on the glass substrate. Appropriately increasing the amount of anhydrous ethanol can promote the cross-linking of titanium micelles, thereby increasing the loading of titanium dioxide; however, adding too much anhydrous ethanol will reduce the concentration of titanium in the sol system, reduce the polymerization rate of titanium micelles, and thus reduce the coating rate of the titanium dioxide film. In Example 7, 63 parts of anhydrous ethanol were most suitable. In Examples 7 and 10-14, too short a calcination time or too low a calcination temperature will result in insufficient curing of the titanium dioxide sol, weak adhesion between the coating and the glass substrate, and problems such as peeling or cracking during subsequent use. Extending the calcination time helps the titanium dioxide sol to fully cure and improves the adhesion between the coating and the glass substrate; however, too long a calcination time may cause thermal stress problems in the glass substrate, leading to cracks or deformation. Too high a calcination temperature will cause structural changes inside the coating, such as grain growth and reduced porosity, thereby affecting the coating performance. In Example 13, when the glass substrate was pretreated with a 14 wt% sodium hydroxide solution, and anhydrous ethanol was added in a total of 63 parts by weight, the calcination temperature was 340°C, and the calcination time was 1.3 h, the resulting insulated energy-saving glass had a visible light transmittance of 66% and a direct solar transmittance of 46%, exhibiting excellent thermal insulation performance and effectively reducing building energy consumption. In Comparative Example 1, no sodium hydroxide solution was used for pretreatment of the glass substrate, resulting in uneven distribution of titanium dioxide sol on the surface of the glass substrate, leading to a decrease in the thermal insulation performance of the resulting insulated energy-saving glass.

[0048] Example 16

[0049] The glass substrate was ultrasonically cleaned in anhydrous ethanol for 20 min to obtain a cleaned glass substrate. The cleaned glass substrate was then ultrasonically cleaned in a 14 wt% sodium hydroxide solution for 2 h, washed with distilled water, and dried at 100℃ for 10 h to obtain a pretreated glass substrate. Two-thirds of the total anhydrous ethanol, 25 parts of tetrabutyl titanate, and 7 parts of glacial acetic acid were added to a flask at 30℃ to obtain mixture one. The remaining one-third of the anhydrous ethanol, 12 parts of deionized water, and 1 part of 1M hydrochloric acid solution were mixed and added dropwise to mixture one to obtain mixture two. The pH of mixture two was 3.5. Mixture two was allowed to stand overnight at room temperature to obtain a titanium dioxide sol. The pretreated glass substrate was added to the titanium dioxide sol, ultrasonicated for 1 h, washed with anhydrous ethanol, dried at 70℃ for 10 h, and calcined at 340℃ for 1.3 h to obtain a coated glass substrate. The total amount of anhydrous ethanol added was 63 parts by weight. The ultrasonic parameters were as follows: ultrasonic frequency 40 kHz, power density 150 W / L.

[0050] By weight, 10 parts of N-isopropylacrylamide were dissolved in 60 parts of ethanol, and 0.08 parts of benzoyl peroxide were added. The mixture was stirred at 400 r / min at room temperature for 30 min to obtain a clear solution. 30 parts of molecular sieve were added to the clear solution for impregnation for 2.5 h and then dried to obtain a mixed material. The mixed material was subjected to a polymerization reaction at 85 °C to obtain a polymerized material. The polymerization reaction time was 20 h. The polymerized material was washed with chloroform and ethanol until the supernatant was free of residual monomers and dried at 60 °C for 2 h to obtain the modified molecular sieve.

[0051] Attapulgite, silica gel powder, and magnesium sulfate additive were mixed evenly in a ratio of 2:1:0.5 to obtain material one; material one was baked at a constant temperature of 128℃ for 1.5 hours, and extruded into spherical particles with a diameter of 2 mm using an extruder, and dried at 110℃ to obtain material two; material two was crushed and passed through a 50-mesh sieve, and calcined at 380℃ for 1 hour to obtain a desiccant.

[0052] A desiccant is filled into the spacer frame to obtain a filled spacer frame; butyl sealant is evenly coated onto the filled spacer frame using a butyl sealant coating machine at a temperature of 135℃, an extrusion pressure of 0.5MPa, and a coating speed of 20m / min to obtain a coated spacer frame; two coated glass substrates are bonded to the coated spacer frame respectively, fixed, and pressed to obtain a rough finished product; structural silicone sealant is applied to the joint between the coated glass substrate and the spacer frame to obtain a glued rough finished product; gas is filled into the glued rough product and sealed to obtain an insulated energy-saving glass; the gas is a mixture of argon and nitrogen in a volume ratio of 3:1.2; the gas volume ratio is 55%-95% of the insulated layer volume; the desiccant filling percentage is 50%; the insulated layer thickness is 6mm.

[0053] Examples 17-34

[0054] The preparation method and parameters of Example 16 are similar, with specific differences shown in Table 3.

[0055] Table 3 Specific preparation parameters for Examples 17-34

[0056] Example 17 Montmorillonite 2:1:0.5 110 380 1 2.5 85 Example 18 Modified molecular sieves 2:1:0.5 110 380 1 2.5 85 Example 19 Modified molecular sieves 3:1:0.5 110 380 1 2.5 85 Example 20 Modified molecular sieves 3:2:0.5 110 380 1 2.5 85 Example 21 Modified molecular sieves 3:2:1 110 380 1 2.5 85 Example 22 Modified molecular sieves 3:2:1.5 110 380 1 2.5 85 Example 23 Modified molecular sieves 4:2:1 110 380 1 2.5 85 Example 24 Modified molecular sieves 4:2:1 130 380 1 2.5 85 Example 25 Modified molecular sieves 4:2:1 150 380 1 2.5 85 Example 26 Modified molecular sieves 4:2:1 180 380 1 2.5 85 Example 27 Modified molecular sieves 4:2:1 150 400 1 2.5 85 Example 28 Modified molecular sieves 4:2:1 150 420 1 2.5 85 Example 29 Modified molecular sieves 4:2:1 150 400 1.5 2.5 85 Example 30 Modified molecular sieves 4:2:1 150 400 1.8 2.5 85 Example 31 Modified molecular sieves 4:2:1 150 400 1.5 2.8 85 Example 32 Modified molecular sieves 4:2:1 150 400 1.5 3 85 Example 33 Modified molecular sieves 4:2:1 150 400 1.5 2.8 100 Example 34 Modified molecular sieves 4:2:1 150 400 1.5 2.8 110

[0057] Comparative Example 2

[0058] Insulating energy-saving glass was prepared according to the method of Example 16, but the difference was that silica gel powder was not added to the desiccant.

[0059] Comparative Example 3

[0060] Insulating energy-saving glass was prepared according to the method of Example 16, but the difference was that no additives were added to the desiccant.

[0061] Comparative Example 4

[0062] Insulating energy-saving glass was prepared according to the method of Example 16, but the difference was that silica gel powder and additives were not added to the desiccant.

[0063] Example 35 Thermal Insulation Performance Test

[0064] The heat transfer coefficient of insulated energy-saving glass was tested according to the method in GB / T22476-2008 "Calculation and determination of steady-state U-value (heat transfer coefficient) of insulated glass"; the results are shown in Table 4.

[0065] Table 4 Thermal insulation performance tests of Examples 13 and 16-34

[0066]

[0067] As shown in Table 4, in Examples 13 and 16-18, changing the type of additive, the desiccant showed the best moisture absorption effect when modified molecular sieve was used as the additive. Modified molecular sieve is a highly porous silicate crystal with strong adsorption capacity, capable of adsorbing various substances, and does not release heat during use, thus maintaining the dryness and stability of the inside of the insulating glass and improving its thermal insulation performance. In Examples 18-23, changing the ratio of attapulgite, silica gel powder, and additives, a ratio of 4:2:1 was most suitable, as the three components could work synergistically to improve the performance of the desiccant, thereby enhancing the thermal insulation performance of the insulating glass. After extruding spherical particles with a diameter of 2mm using an extruder, drying is required to solidify the material. In Examples 23-26, excessively low drying temperatures led to incomplete curing, resulting in unreacted chemical bonds or residual moisture inside the material, affecting the desiccant's moisture absorption performance; while excessively high drying temperatures could cause the material surface to dry too quickly, forming a hard shell, preventing effective drainage of internal moisture and also affecting the desiccant's moisture absorption performance. In Example 25, a drying temperature of 150°C facilitates the formation and stabilization of internal chemical bonds in the material, enhancing the moisture absorption performance of the desiccant and thus improving the thermal insulation performance of the insulating glass. In Examples 25 and 27-30, changing the calcination temperature and time allows for adjustments. An appropriate calcination temperature increases the specific surface area and pore volume of the material, thereby improving its adsorption capacity; however, excessively high calcination temperatures can cause the collapse and blockage of the internal pore structure, reducing the specific surface area and pore volume. If the calcination time is too short, the internal reaction may be incomplete, affecting the moisture absorption performance of the desiccant; if the calcination time is too long, excessive sintering may occur, resulting in a denser crystal structure and reduced pore size, which also reduces the moisture absorption performance of the desiccant. In Examples 29 and 31-34, changing the impregnation time and polymerization temperature during the preparation of the modified molecular sieve allows the polymerization reaction to proceed at a faster rate while maintaining a higher polymer molecular weight, resulting in a modified molecular sieve that can rapidly adsorb water vapor. In Example 31, when modified molecular sieves were used as additives, and the ratio of attapulgite, silica gel powder, and additives was 4:2:1, the drying temperature was 150°C, the calcination temperature was 400°C, the calcination time was 1.5 h, the impregnation time was 2.8 h, and the polymerization temperature was 85°C, the resulting desiccant exhibited the best drying effect. When filled into insulated glass, it effectively adsorbed moisture and residual organic matter inside the insulated glass, reducing the thermal conductivity of the air layer inside the insulated glass, with a heat transfer coefficient of 0.90 W / m. 2 • K, the thermal insulation performance of the insulated glass is improved, thereby enhancing energy efficiency. In Comparative Examples 2-4, the desiccant was prepared without silica gel powder, with additives, with silica gel powder and with additives respectively. The pore structure and specific surface area of ​​the desiccant were affected, resulting in a significant decrease in the adsorption capacity of the desiccant and failing to effectively improve the thermal insulation performance of the insulated glass.

[0068] Example 36

[0069] The glass substrate was ultrasonically cleaned in anhydrous ethanol for 20 min to obtain a cleaned glass substrate. The cleaned glass substrate was then ultrasonically cleaned in a 14 wt% sodium hydroxide solution for 2 h, washed with distilled water, and dried at 100℃ for 10 h to obtain a pretreated glass substrate. Two-thirds of the total anhydrous ethanol, 25 parts of tetrabutyl titanate, and 7 parts of glacial acetic acid were added to a flask at 30℃ to obtain mixture one. The remaining one-third of the anhydrous ethanol, 12 parts of deionized water, and 1 part of 1M hydrochloric acid solution were mixed and added dropwise to mixture one to obtain mixture two. The pH of mixture two was 3.5. Mixture two was allowed to stand overnight at room temperature to obtain titanium dioxide sol. The pretreated glass substrate was added to the titanium dioxide sol, ultrasonicated for 1 h, washed with anhydrous ethanol, dried at 70℃ for 10 h, and calcined at 340℃ for 1.3 h to obtain a coated glass substrate. The total amount of anhydrous ethanol added was 63 parts. The ultrasonic parameters were as follows: ultrasonic frequency 40 kHz, power density 150 W / L.

[0070] By weight, 10 parts of N-isopropylacrylamide were dissolved in 60 parts of ethanol, and 0.08 parts of benzoyl peroxide were added. The mixture was stirred at 400 r / min at room temperature for 30 min to obtain a clear solution. 30 parts of molecular sieve were added to the clear solution for impregnation for 2.8 h and then dried to obtain a mixed material. The mixed material was subjected to a polymerization reaction at 85 °C to obtain a polymerized material. The polymerization reaction time was 20 h. The polymerized material was washed with chloroform and ethanol until the supernatant was free of residual monomers and dried at 60 °C for 2 h to obtain a modified molecular sieve.

[0071] Attapulgite, silica gel powder, and additive-modified molecular sieve were mixed evenly in a ratio of 4:2:1 to obtain material one; material one was baked at a constant temperature of 128℃ for 1.5h, and extruded into spherical particles with a diameter of 2mm using an extruder, and dried at 150℃ to obtain material two; material two was crushed and passed through a 50-mesh sieve, and calcined at 400℃ for 1.5h to obtain a desiccant.

[0072] A desiccant is filled into the spacer frame to obtain a filled spacer frame; butyl sealant is evenly coated onto the filled spacer frame using a butyl sealant coating machine at a temperature of 140℃, an extrusion pressure of 0.5MPa, and a coating speed of 20m / min to obtain a coated spacer frame; two coated glass substrates are bonded to the coated spacer frame respectively, fixed, and pressed to obtain a rough finished product; structural silicone sealant is applied to the joint between the coated glass substrate and the spacer frame to obtain a glued rough finished product; gas is filled into the glued rough product and sealed to obtain an insulated energy-saving glass; the gas is a mixture of argon and nitrogen in a volume ratio of 3:1.2; the gas volume ratio is 55%-95% of the insulated layer volume; the desiccant filling percentage is 50%; the insulated layer thickness is 6mm.

[0073] Examples 37-47

[0074] The preparation method and parameters of Example 36 are similar, with specific differences shown in Table 5.

[0075] Example 48 Thermal Insulation Performance Test

[0076] The heat transfer coefficient of insulated energy-saving glass was tested according to the method in GB / T22476-2008 "Calculation and determination of steady-state U-value (heat transfer coefficient) of insulated glass"; the results are shown in Table 5.

[0077] Table 5 Thermal insulation performance tests of Examples 31, 36-47

[0078]

[0079] As shown in Table 5, in Examples 31 and 36-38, if the coating temperature is too high, the viscosity of the butyl rubber decreases, its fluidity becomes too strong, and it is difficult to control the coating thickness and width; if the coating temperature is too low, the viscosity of the butyl rubber increases, its fluidity deteriorates, and it is difficult to coat it evenly on the spacer frame, affecting the coating effect. In Example 36, when the coating temperature is 140℃, the viscosity of the butyl rubber decreases, its fluidity increases, and a uniform and continuous coating can be formed on the spacer frame, improving the sealing performance and preventing impurities such as air and moisture from entering the insulating layer and damaging its thermal insulation effect. In Examples 36 and 39-42, if the extrusion pressure is too high, the extrusion speed of the butyl rubber increases, leading to uneven coating, bubbles, or glue breaks. The butyl rubber cannot form a continuous and uniform sealing layer, affecting its thermal insulation performance and thus the overall thermal insulation effect of the insulating glass. In Example 41, an extrusion pressure of 1.2 MPa is optimal. The application speed determines the area covered by butyl sealant per unit time. In Examples 41 and 43-45, excessively fast application speeds lead to uneven coating, resulting in missed areas or thin coatings, which reduces sealing performance and affects the thermal insulation performance of the insulated glass. In Examples 43 and 46-47, changing the type of structural adhesive and using silicone sealant as the structural adhesive resulted in better sealing performance and higher water vapor permeability resistance, thus improving the thermal insulation effect of the insulated layer. In Example 43, applying butyl sealant to the spacer frame using a butyl sealant coating machine at a temperature of 140°C, an extrusion pressure of 1.2 MPa, and an application speed of 25 m / min yielded the best sealing performance in the insulated glass, with a thermal transfer coefficient of 0.84 W / m. 2 ·K.

[0080] Example 49

[0081] The glass substrate was ultrasonically cleaned in anhydrous ethanol for 20 min to obtain a cleaned glass substrate. The cleaned glass substrate was then ultrasonically cleaned in a 14 wt% sodium hydroxide solution for 2 h, washed with distilled water, and dried at 100℃ for 10 h to obtain a pretreated glass substrate. Two-thirds of the total anhydrous ethanol, 25 parts of tetrabutyl titanate, and 7 parts of glacial acetic acid were added to a flask at 30℃ to obtain mixture one. The remaining one-third of the anhydrous ethanol, 12 parts of deionized water, and 1 part of 1M hydrochloric acid solution were mixed and added dropwise to mixture one to obtain mixture two. The pH of mixture two was 3.5. Mixture two was allowed to stand overnight at room temperature to obtain a titanium dioxide sol. The pretreated glass substrate was added to the titanium dioxide sol, ultrasonicated for 1 h, washed with anhydrous ethanol, dried at 70℃ for 10 h, and calcined at 340℃ for 1.3 h to obtain a coated glass substrate. The total amount of anhydrous ethanol added was 63 parts by weight. The ultrasonic parameters were as follows: ultrasonic frequency 40 kHz, power density 150 W / L.

[0082] By weight, 10 parts of N-isopropylacrylamide were dissolved in 60 parts of ethanol, and 0.08 parts of benzoyl peroxide were added. The mixture was stirred at 400 r / min at room temperature for 30 min to obtain a clear solution. 30 parts of molecular sieve were added to the clear solution for impregnation for 2.8 h and then dried to obtain a mixed material. The mixed material was subjected to a polymerization reaction at 85 °C to obtain a polymerized material. The polymerization reaction time was 20 h. The polymerized material was washed with chloroform and ethanol until the supernatant was free of residual monomers and dried at 60 °C for 2 h to obtain a modified molecular sieve.

[0083] Attapulgite, silica gel powder, and additive-modified molecular sieve were mixed evenly in a ratio of 4:2:1 to obtain material one; material one was baked at a constant temperature of 128℃ for 1.5h, and extruded into spherical particles with a diameter of 2mm using an extruder, and dried at 150℃ to obtain material two; material two was crushed and passed through a 50-mesh sieve, and calcined at 400℃ for 1.5h to obtain a desiccant.

[0084] A desiccant is filled into the spacer frame to obtain a filled spacer frame; butyl sealant is evenly coated onto the filled spacer frame using a butyl sealant coating machine at a temperature of 140℃, an extrusion pressure of 1.2MPa, and a coating speed of 25m / min to obtain a coated spacer frame; two coated glass substrates are bonded to the coated spacer frame respectively, fixed, and pressed to obtain a rough finished product; structural silicone sealant is applied to the joint between the coated glass substrate and the spacer frame to obtain a glued rough finished product; gas is filled into the glued rough product and sealed to obtain an insulated energy-saving glass; the gas is a mixture of argon and nitrogen in a volume ratio of 4:1.2; the gas volume ratio is 55%-95% of the insulated layer volume; the desiccant filling percentage is 50%; the insulated layer thickness is 6mm.

[0085] Examples 50-56

[0086] The preparation method and parameters of Example 45 are similar, with specific differences shown in Table 6.

[0087] Example 57 Thermal Insulation Performance Test

[0088] The heat transfer coefficient of insulated energy-saving glass was tested according to the method in GB / T22476-2008 "Calculation and determination of steady-state U-value (heat transfer coefficient) of insulated glass"; the results are shown in Table 6.

[0089] Table 6 Thermal insulation performance tests of Examples 43, 49-56

[0090]

[0091] Argon is an inert gas with low thermal conductivity, and filling it with argon can significantly improve the thermal insulation performance of insulated glass. However, argon is expensive. Nitrogen also has low thermal conductivity and is inexpensive, resulting in lower-cost insulated glass filled with nitrogen. Furthermore, nitrogen is highly stable and less prone to leakage. Table 6 shows that in Examples 43 and 49-56, mixing argon and nitrogen to fill the insulated layer allows the insulated glass to achieve excellent thermal insulation, environmental performance, and lower cost. In Example 50, the optimal effect is achieved when the volume ratio of argon to nitrogen is 4:2.2. In addition to improving thermal insulation, filling the insulated layer with gas can also reduce moisture inside the glass, slow down spacer oxidation and desiccant aging, and extend the glass's lifespan. In Examples 50 and 53-54, if too little gas is filled, the thermal insulation effect of the insulated glass will decrease, making it difficult to control indoor temperature and humidity and increasing energy consumption. Furthermore, insufficient gas filling may cause condensation and fogging inside the glass, accelerating the oxidation of the spacer frame and the aging of the desiccant. In Example 56, excessive gas filling does not further improve the thermal insulation performance; instead, it increases the internal pressure of the glass, increasing the risk of glass breakage. In Example 55, when the insulated layer is filled with 88% gas, with a volume ratio of argon to nitrogen of 4:2.2, the resulting insulated energy-saving glass exhibits the best thermal insulation performance and significantly improved energy-saving effect, with a heat transfer coefficient of 0.78 W / m². 2 ·K.

[0092] Example 58

[0093] The glass substrate was ultrasonically cleaned in anhydrous ethanol for 20 min to obtain a cleaned glass substrate. The cleaned glass substrate was then ultrasonically cleaned in a 14 wt% sodium hydroxide solution for 2 h, washed with distilled water, and dried at 100℃ for 10 h to obtain a pretreated glass substrate. Two-thirds of the total anhydrous ethanol, tetrabutyl titanate, and glacial acetic acid were added to a flask at 30℃ to obtain mixture one. The remaining one-third of the anhydrous ethanol, deionized water, and 1M hydrochloric acid solution were mixed and added dropwise to mixture one to obtain mixture two. The pH of mixture two was 3.5. Mixture two was allowed to stand overnight at room temperature to obtain titanium dioxide sol. The pretreated glass substrate was added to the titanium dioxide sol, ultrasonicated for 1 h, washed with anhydrous ethanol, dried at 70℃ for 10 h, and calcined at 340℃ for 1.3 h to obtain a coated glass substrate. The total amount of anhydrous ethanol added was 63 parts by weight.

[0094] By weight, 10 parts of N-isopropylacrylamide were dissolved in 60 parts of ethanol, and 0.08 parts of benzoyl peroxide were added. The mixture was stirred at 400 r / min at room temperature for 30 min to obtain a clear solution. 30 parts of molecular sieve were added to the clear solution for impregnation for 2.8 h and then dried to obtain a mixed material. The mixed material was subjected to a polymerization reaction at 85 °C to obtain a polymerized material. The polymerization reaction time was 20 h. The polymerized material was washed with chloroform and ethanol until the supernatant was free of residual monomers and dried at 60 °C for 2 h to obtain a modified molecular sieve.

[0095] Attapulgite, silica gel powder, and additive-modified molecular sieve were mixed evenly in a ratio of 4:2:1 to obtain material one; material one was baked at a constant temperature of 128℃ for 1.5h, and extruded into spherical particles with a diameter of 2mm using an extruder, and dried at 150℃ to obtain material two; material two was crushed and sieved, and calcined at 400℃ for 1.5h to obtain a desiccant.

[0096] A desiccant is filled into the spacer frame to obtain a filled spacer frame; butyl sealant is evenly coated onto the filled spacer frame using a butyl sealant coating machine at a temperature of 140℃, an extrusion pressure of 1.2MPa, and a coating speed of 25m / min to obtain a coated spacer frame; two coated glass substrates are bonded to the coated spacer frame respectively, fixed, and pressed to obtain a rough finished product; structural silicone sealant is applied to the joint between the coated glass substrate and the spacer frame to obtain a glued rough finished product; gas is filled into the glued rough product and sealed to obtain an insulated energy-saving glass; the gas is a mixture of argon and nitrogen in a volume ratio of 4:2.2; the gas content is 85%; the desiccant filling percentage is 60%; and the hollow layer thickness is 6mm.

[0097] Examples 59-63

[0098] The preparation method and parameters of Example 58 are similar, with specific differences shown in Table 7.

[0099] Example 64 Thermal Insulation Performance Test

[0100] The heat transfer coefficient of insulated energy-saving glass was tested according to the method in GB / T22476-2008 "Calculation and determination of steady-state U-value (heat transfer coefficient) of insulated glass"; the results are shown in Table 7.

[0101] Table 7 Thermal insulation performance tests of Examples 55, 58-63

[0102]

[0103] As shown in Table 7, in Examples 55 and 58-60, insufficient desiccant filling percentage leads to inadequate dehumidification capacity, failing to fully absorb moisture inside the insulated glass, resulting in excessively high humidity inside the insulated glass. This may cause fogging, condensation, and other phenomena, thus reducing the thermal insulation performance of the insulated glass. In Example 59, the insulated glass with the best thermal insulation performance is achieved when the desiccant filling percentage is 75%. In Examples 59 and 61-63, if the insulated layer thickness is too low, it cannot effectively block heat transfer, resulting in large indoor temperature fluctuations and poor thermal insulation performance of the insulated glass. Increasing the insulated layer thickness can more effectively block heat conduction through the air, thereby reducing the possibility of heat transfer to the room. However, when the thickness exceeds a certain range, an excessively large insulated layer will lead to enhanced air convection, thus weakening the thermal insulation effect. In Example 62, the combination of a 14mm insulated glass layer and a 75% desiccant filling effectively maintains a stable glass surface temperature, reduces heat transfer paths, minimizes condensation and fogging caused by excessive temperature differences, and keeps the interior of the insulated glass dry. The combined effect significantly improves the thermal insulation performance of the insulated glass, achieving a heat transfer coefficient of 0.74 W / m². 2 •K, energy-saving effect is improved.

[0104] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for manufacturing insulated energy-saving glass, characterized in that: The manufacturing method is as follows: A glass substrate is pretreated with sodium hydroxide solution and then added to titanium dioxide sol, followed by calcination to obtain a coated glass substrate; a desiccant is prepared from attapulgite, silica gel powder, and additives; the desiccant is filled into a spacer frame to obtain a filled spacer frame; butyl rubber is uniformly coated onto the filled spacer frame to obtain an adhesive-coated spacer frame; two coated glass substrates and the adhesive-coated spacer frame constitute a rough finished product; structural adhesive is applied to the junction of the coated glass substrate and the adhesive-coated spacer frame to obtain an adhesive-filled rough finished product; argon and nitrogen are introduced into the adhesive-filled rough product and sealed to obtain the insulating energy-saving glass.

2. The method for manufacturing hollow energy-saving glass according to claim 1, characterized in that: The method for preparing the coated glass substrate is as follows: the glass substrate is cleaned and then sonicated in a sodium hydroxide solution, and dried to obtain a pretreated glass substrate; anhydrous ethanol, tetrabutyl titanate and glacial acetic acid are mixed to obtain mixture one; the anhydrous ethanol, deionized water and hydrochloric acid solution are mixed and added dropwise to mixture one to obtain mixture two, and left to stand overnight to obtain the titanium dioxide sol; the pretreated glass substrate is added to the titanium dioxide sol, sonicated and then washed with anhydrous ethanol, dried and calcined to obtain the coated glass substrate.

3. The method for manufacturing a hollow energy-saving glass according to claim 1, characterized in that: The desiccant is prepared as follows: the attapulgite, the silica gel powder and the additive are mixed to obtain material one; material one is baked and then extruded to obtain material two; material two is crushed, sieved and then calcined to obtain the desiccant.

4. The method for manufacturing insulated energy-saving glass according to claim 1, characterized in that: The additive is one of activated alumina, magnesium sulfate, montmorillonite, and modified molecular sieve.

5. The method for manufacturing an insulating energy-saving glass according to claim 4, characterized in that: The modified molecular sieve is prepared as follows: N-isopropylacrylamide is dissolved in ethanol, benzoyl peroxide is added, and the mixture is stirred to obtain a clear solution; molecular sieve is added to the clear solution for impregnation and then dried to obtain a mixed material; the mixed material is subjected to a polymerization reaction to obtain a polymeric material; the mixture is washed and dried to obtain the modified molecular sieve.

6. The method for manufacturing a hollow energy-saving glass according to claim 1, characterized in that: The structural adhesive is one of silicone adhesive, polyurethane adhesive, or acrylic adhesive.

7. The method for manufacturing a hollow energy-saving glass according to claim 1, characterized in that: The two coated glass substrates have a hollow layer between them; the thickness of the hollow layer is 6-15mm; and the desiccant filling percentage is 50%-85%.

8. A type of insulated energy-saving glass manufactured by the method described in claim 1, characterized in that: The insulated energy-saving glass includes a glass substrate, a spacer frame, butyl sealant, structural adhesive, desiccant, argon, and nitrogen.

Citation Information

Patent Citations

  • Energy-saving films, laminated glass, insulated glass and their applications

    CN109534691B

  • A hollow energy-saving glass and its manufacturing method

    CN116239318B